2017
DOI: 10.1016/j.neuron.2017.08.015
|View full text |Cite|
|
Sign up to set email alerts
|

The Spatiotemporal Organization of the Striatum Encodes Action Space

Abstract: SummaryActivity in striatal direct- and indirect-pathway spiny projection neurons (SPNs) is critical for proper movement. However, little is known about the spatiotemporal organization of this activity. We investigated the spatiotemporal organization of SPN ensemble activity in mice during self-paced, natural movements using microendoscopic imaging. Activity in both pathways showed predominantly local but also some long-range correlations. Using a novel approach to cluster and quantify behaviors based on conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
222
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(278 citation statements)
references
References 43 publications
(86 reference statements)
27
222
2
Order By: Relevance
“…Recently, in freely moving animals, it was reported that both SPN populations become active in localized compact groups of synchronized neurons, that alternate their activity over time (Barbera et al, 2016;Klaus et al, 2017;London et al, 2018), these results are similar to previous slice recordings treated with NMDA . In contrast, slices from DA-depleted animals report neuronal activity locked into a dominant network state with reduced alternations between the assemblies (Jaidar et al, 2010;Lopez-Huerta et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Recently, in freely moving animals, it was reported that both SPN populations become active in localized compact groups of synchronized neurons, that alternate their activity over time (Barbera et al, 2016;Klaus et al, 2017;London et al, 2018), these results are similar to previous slice recordings treated with NMDA . In contrast, slices from DA-depleted animals report neuronal activity locked into a dominant network state with reduced alternations between the assemblies (Jaidar et al, 2010;Lopez-Huerta et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with the coordinated synchronous activation of indirect and direct SPNs necessary for the selection, initiation and performance of a particular movement, it has been reported that when the animal is not moving, SPNs remain inactive, but become coactive during movement initiation (Cui et al, 2013;Klaus et al, 2017). With the increase in the number of active cells and peaks of synchrony observed in DA-depleted tissue, we hypothesized that in the absence of DA, the observed increase in synchronous activation of large sets of striatal neurons could be responsible for the animal's motor impairments, such as deviated posture and persistent spontaneous turning (Costall, Marsden, Naylor, & Pycock, 1976;Dunnett & Iversen, 1982), Figure 1e.…”
Section: Simultaneous Photoactivation Of Direct and Indirect Pathwamentioning
confidence: 67%
See 1 more Smart Citation
“…The description of the innervation from the whole prefrontal cortex into segregated striatal areas, led to the exploration of basal ganglia functions associated with prefrontal cortical functions in monkeys (Graybiel, 1991;Romo et al, 1992;Joel & Weiner, 1994;Jaeger et al, 1995;Afifi, 2003). Some recently described striatal functions related to prefrontal cortical integration in rats that are of interest to this review, include motivational drive (Kreitzer & Berke, 2011), generation of self-paced movements (Klaus et al, 2017), and context-dependent facilitation of appropriate movements (Kreitzer & Berke, 2011), as well as learning involved in risk-based decisionmaking (Leblond et al, 2011), solution of cognitive conflicts between actions (Laurent et al, 2017), selection of action alternatives (Canales & Graybiel, 2000), decision-making particularly, in relation to the effort invested to obtain a reward (Carvalho Poyraz et al, 2016) and cost-benefit decision-making (Friedman et al, 2015).…”
Section: Basal Ganglia and Striatummentioning
confidence: 99%
“…Recent advances in single-photon-based miniscope technology have further enabled imaging of neural ensemble activities in freely moving animals (Cai et al, 2016; Flusberg et al, 2008; Ghosh et al, 2011), thereby allowing circuits involved in a rich repertoire of animal behaviors to be examined. For example, this technology has been successfully used in probing dynamics of neural circuits involved in innate behaviors (Betley et al, 2015; Douglass et al, 2017; Jennings et al, 2015), decision making (Pinto and Dan, 2015; Carvalho Poyraz et al, 2016), motor control (Klaus et al, 2017), learning and memory (Grewe et al, 2017; Kamigaki and Dan, 2017; Kitamura et al, 2017; Roberts et al, 2017; Roy et al, 2017; Xu et al, 2016), social memory (Okuyama et al, 2016), hippocampal place coding (Ziv et al, 2013), sleep (Cox et al, 2016; Weber and Dan, 2016), bird song (Markowitz et al, 2015), and pathological processes (Berdyyeva et al, 2016). …”
Section: Introductionmentioning
confidence: 99%